THE INFLUENCE OF PRODUCT KNOWLEDGE AND WORD OF MOUTH ON THE DECISION TO BECOME A MEMBER OF BMT AL-ISHLAH JAMBI CITY - Neili Khoerun Ni'mah; Sissah sissah; Jevi Saputra (Universitas Islam Darul 'ulum Lamongan, 2025)
Abstract Indonesia is a country where the majority of the population is Islamic, therefore the birth of the micro-shariah financial institutions can be a solution to the development of the shariah banking that is still centralized to the middle up society. This research aims to identify and analyze the impact of product knowledge and word of mouth on membership decisions. The respondents used in this study are members of BMT Al-Ishlah Jambi City. The method used in this research is the quantitative method. The data was collected through a questionnaire using the likert scale, then the number of samples used was 85 respondents. The analytical technique used is double linear regression analysis. Partial and simultaneous test results of testing the product knowledge (X1) and word of mouth (X2) variables partially and simultaneously show that there is a significant influence on the decision to become a member (Y), and variable X has an influence of 39,5% on variable Y.